Musical creation of "human" as a sense-making sensuous way of forming a cultural space - I. V. Zhyvohliadova, (Ukrainian Cultural Studies, 2019)
The article analyzes the specificity of revealing anthropo-creative principles of European culture as a musical practice of humanity. If we under- stand culture as a source, space, and the result of the spiritually-practical experience of mankind, then music appears as a specific, holistic system of specification and representation of this experience, a phenomenon that reflected the uniqueness and depth of the humanity world, a specifically sensual way of joining an intersubjective experience of rhythmization and harmonization of the human being. The expressive possibilities of language means of music art are considered in the context of the overall process of making a musical sound of human living space, the development of artistic practices of worldview and the world perception of medieval Christian culture in particular.
Keywords: Christian culture, Byzantine culture, spiritual music, artistic worldview and world perception, musical sensibility, musical literary language, musical forms, liturgy